Consumer Protection (Fair Trading) Act : implications since its inception. - Lin, Yaowei. (2008)
This paper explores the implications of the Fair Trading Act since its inception. Consumers' attitudes and perceptions towards the act are examined and its impact for retailers/consumers evaluated. Some examples of consumer protection systems are identified and the possibility of application to the Singapore context is assessed.